Mentoring for the Development of MSMEs in Menes District through the Making of Halal Certification - Indri Wisdiarti Anugraheni (Bulletin of Social Studies and Community Development, 2024)
Abstract: One of the drivers of the economy in Indonesia today is the consistent increase in MSMEs locally and nationally. In running MSMEs, there is a need for proper development and management so that they are still able to develop and advance in their business. In every economic sector, MSMEs (micro, small and medium enterprises) are autonomous production sectors run by the private sector or legal entities. Since Indonesia is predominantly Muslim, it is necessary to ensure that the products sold by MSMEs are halal. This service aims to assist MSME players in obtaining halal certification to increase consumer confidence. The "practical learning" approach, which is applied in community service activities (PkM), offers MSME partners technical assistance through one-on-one coaching. The expansion of MSMEs in halal certification support was the outcome of this PkM initiative. It is envisaged that with this help, sales volumes and consumer trust in the completeness of halal certification will increase.     Keywords: MSMEs, mentoring, halal certificate.